Music as Collective Invention: A Social Network Analysis of Composers. (March 2015) - McAndrew, Siobhan; Everett, Martin
Composers generally write music alone, and we commonly understand the great figures of classical music as singular geniuses. Even where composers' social networks and friendships are of contextual interest, it is arguable that their association with other musicians arises because they choose to socialize with similar others. However, it is also possible that creative work, even for artists as solitary as composers, depends significantly on interaction and collaboration. Certain periods and places are considered hotspots of creativity where new musical ideas are shared and movements arise. In this paper we consider the case of British classical composition, both as an example of a music network, and to contribute to debates in music history.